A new syndrome of symphalangism, multiple frenula, postaxial polydactyly, dysplastic ears, dental anomalies, and exclusion of NOG and GDF5 - Kantaputra P.N. (2014)
A Thai girl with a unique combination of limb and craniofacial anomalies is reported. Manifestations include blepharoptosis; prominent nose; hypodontia; multiple, hyperplastic frenula; and dysplastic ears. Limb anomalies include short stature, postaxial polydactyly of both hands and the left foot, proximal and distal symphalangism of fingers, and congenital absence of the distal phalanges of toes 2-5. Mutation analyses of NOG and GDF5, the genes responsible for symphalangism-related syndromes, were negative. © 2003 Wiley-Liss, Inc.